Channel mobility drives a diverse stratigraphic architecture in the dryland Mojave River (California, USA). Issue 8 (4th March 2020) - Ielpi, Alessandro; Lapôtre, Mathieu G.A.; Finotello, Alvise; Ghinassi, Massimiliano; D'Alpaos, Andrea
Abstract: The links between flood frequency and rates of channel migration are poorly defined in the ephemeral rivers typical of arid regions. Exploring these links in desert fluvial landscapes would augment our understanding of watershed biogeochemistry and river morphogenesis on early Earth (i.e. prior to the greening of landmasses). Accordingly, we analyse the Mojave River (California), one of the largest watercourses in the Great Basin of the western United States. We integrate discharge records with channel‐migration rates derived from dynamic time‐warping analysis and chronologically calibrated subsidence rates, thereby constraining the river's formative conditions. Our results reveal a slight downstream decrease in bankfull discharge on the Mojave River, rather than the downstream increase typically exhibited by perennial streams. Yet, the number of days per year during which the channel experiences bankfull or higher stages is roughly maintained along the river's length. Analysis of historical peak flood records suggests that the incidence of channel‐formative events responds to modulation in watershed runoff due to the precipitation in the river's headwaters over decades to centuries. Our integrated analysis finally suggests that, while maintaining hydraulic geometries that are fully comparable with many other rivers worldwide, ephemeral desert rivers akin to the Mojave are capable of generating a surprisingly wide range of depositional geometries in the stratigraphic record. © 2020 John Wiley & Sons, Ltd. Abstract : Desert rivers are increasingly recognized as key to understanding landscape morphogenesis on ancient barren planetary surfaces such as early Earth. An integrated analysis of hydrology, time‐lapse remote sensing of channel migration, and subsidence rates is performed in the watershed of the Mojave River of California. We show that desert channels dynamically adapt their hydrologic section to fading discharge downstream, and are capable of generating a surprisingly broad range of stratigraphic architectures in the rock record.